GENOTYPE-ENVIRONMENT INTERACTION IN SPRING WHEAT (Triticum aestivum) OF BANGLADESH - Islam, M. S.; Halder, T.; Hossain, J.; Mahmud, F.; Rahman, J. (Bangladesh Journal of Plant Breeding and Genetics, 2015)
A field study was conducted to select suitable genotype(s) for varying planting dates and to compare the average performance of the genotypes in different environments. The experiment was conducted at the farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh with ten (nine Triticum aestivum and one Triticum turgidum) wheat genotypes. The genotypes were planted at three different dates during November 2012 to March 2013. Analysis of variance for the genotypes showed significant variation which revealed the presence of considerable amount of genetic variability among different genotypes. Significant genotype x environment interaction was obtained for all studied characters and those were tested against pooled error. Environment + (genotype ^ environment) component and genotype ^ environment (linear) component also showed significant variation and the genotypes performed differently in different environments. Except pooled deviation of linear components of genotype-environment interaction were significant for all the characters. So the differences in stability for different characters were due to the linear response and not for non-linear function. Considering all the characters, genotypes G4, G6, G9 performed better in overall environments. The genotype G10 performed better in poor condition whereas G7 performed better in favorable environment. Among three different sowing dates, optimum sowing (sowing at 20 November, 2012) performed better for most of the genotypes and gradually decreased with late sowing.